P1011ATHE SGTL-2 INHIBITORS DECREASE THE MORTALITY AND PROGRESSION OF CHRONIC KIDNEY DISEASE (CKD) IN TYPE 2 DIABETES PATIENTES. SYSTEMATIC REVIEW AND META-ANALYSIS OF THE LITERATURE. (6th June 2020) - Cabrera, Sebastian; Torres, Ruben; Elgueta, Leticia; Segovia, Erico; Sanhueza, Maria Eugenia; Boltansky, Andres; Alvo, Miriam
Abstract: Background and Aims: Diabetic nephropathy is one of the main causes of chronic kidney disease (CKD) in the world. In the past years new studies using SGLT-2 inhibitors in diabetic patients have shown benefit in both mortality and progression of CKD. However, these works show heterogeneity between studies regarding the severity of CKD of patients included. All above complicates the interpretation of the benefits of SGLT-2 inhibitors. Method: We did a systematic search of the literature in PUBMED, EMBASE, Cochrane CENTRAL trials database and in references of the selected studies. Terms used for the search were Canaglifozin, Dapaglifozin, Ertuglifozin, Empaglifozin, diabetes, mortality and CKD. Search included studies in all languages. We selected only randomized and controlled studies that reported mortality and relevant renal outcomes (doubling serum creatinine or decrease in eGFR> 40%, need for renal replacement or renal death). We included studies until September 30, 2019. For the meta-analysis, a Mantel-Haenszel model of random effects was used. The software Review Manager, Version 5.3 The Cochrane Collaboration, 2014 was used. Results: We obtained results from 142 studies, fifteen studies met the selected criteria, but only four reported mortality and renal outcomes (EMPA-REG, CANVAS, CREDENCE AND DECLARE-TIMI 58). A total of 38, 721 patients (SGTL2 inhibitors n = 21, 264 and control n = 17, 457) were included for the analysis. The EMPA-REG study used Empaglifozin, the CANVAS and CREDENCE studies used Canaglifozin and the DECLARE-TIMI 58 used Dapaglifozin. All studies were funded by pharmaceutical laboratories.The average age range of the studies was between 62 to 67 years. The percentage of patients with eGFR <60ml/min were 26%, 20%, 60% and 7% for the EMPA-REG, CANVAS, CREDENCE and DECLARE-TIMI 58 studies respectively.Mortality was lower in patients who used SGTL2 inhibitors OR 0.86 (CI 0.80-0.94) Figure 1 . Renal outcomes were also lower in patients who used SGTL-2 inhibitors OR 0.69 (CI 0.60-0.78) Figure 2 . We assessed whether the effect was related to the severity of the CKD taking out the work with patients with more severe CKD (CREDENCE study), the effect on mortality did not change OR 0.87 (CI 0.80-0.95) as well as renal outcome OR 0.66 (CI 0.52- 0.83) . Conclusion: The SGTL-2 inhibitors decrease mortality and improve renal outcomes in patients with diabetic nephropathy. These benefits remain in patients with less severe CKD.